Der Begriff der Aura und einer Kunst ohne Aura im Werk von Walter Benjamin - Loots, François (German Language and Literature, 2016)
Walter Benjamin formulated the concept of the aura in 1930 while experimenting with hashish. He describes an aura as the essence of an object that is only present in the act of perception. The aura changes from one occurrence of its perception to another. After the hashish trance, the perceiver can not remember the essence of an object - it's aura. The aura has an ambiguity, as well as various meanings in Benjamin's works: a) The aura is used in bourgeois art appreciation and criticism as a criteria to access art. Aura refers to subjective perception or ability, the paradigm of enlightenment. b) The aura is the unique perception of the essence or materiality of an object, one that cannot be represented by means of the signification of language. c) The aura exists in perception, therefore in the relationship between subject and object. d) Benjamin attributes perception of the aura as close, yet distanced in order to describe an auratic perception. e) An auratic perception exists outside of everyday life/routine and only as an autonomous artistic perception. f) An experience can be auratic in so far as an individual can understand the essence of his/her environment in relation to history. By postulating an auratic experience that grasps materiality in its totality Benjamin 4uestions the position of the subject in German Idealism, epitomised by Hegel's practical idea. At the same time Benjamin realises that materiality cannot be represented in its totality in the discourse of signification. Thereby the aura can only gain a metaphoric access to representation. Technology denies any auratic perception or experience, as such the auratic exists only in the hypothesis of a historical origin, such as a metaphysical paradisical condition. The commodity structure stands as a paradigm for modern perception and experience. Commodity fetishism denies the subject an auratic interaction and the relation between subject and object is phantasmagoria!. An auratic perception or experience is replaced by one determined by technology. Benjamin calls the latter one of actuality. Thereby the commodity denies an experience leading to the concept of totality. Benjamin's formulation of the concept of the aura has been seen as his turn to Marxism. A clear demarcation has been drawn between his metaphysical and Marxist writings. My thesis argues that such a division is inadequate and that the common demoninator between Benjamin's earlier and later work has not been analysed sufficiently. Bibliography: pages 225-236.